1984
DOI: 10.3171/jns.1984.60.1.0014
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arteriovenous malformations

Abstract: To address the problems of surgical risk versus natural risk associated with cerebral arteriovenous malformations (AVM's), and the role of the intravascular operative approach, the authors have assessed a 20-year experience with 450 patients. Results of direct surgery in 90 patients indicate that for the smaller AVM's (Grades I and II), mortality and morbidity rates are lower than a reasonably projected natural risk. Hence, these patients are candidates for surgery in most instances. However, for more extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Recurrence is definitely more common in children than in adults. The early evolution of AVMs is consistent with the diffuse patterns of arteriovenous shunting observed in children as opposed to the more distinct fistulous pattern seen in adults 13) . If more mature AVMs develop along a continuum as the brain develops, children are more likely to have immature vasculature as part of their AVM.…”
Section: Discussionsupporting
confidence: 62%
“…Recurrence is definitely more common in children than in adults. The early evolution of AVMs is consistent with the diffuse patterns of arteriovenous shunting observed in children as opposed to the more distinct fistulous pattern seen in adults 13) . If more mature AVMs develop along a continuum as the brain develops, children are more likely to have immature vasculature as part of their AVM.…”
Section: Discussionsupporting
confidence: 62%
“…Few authors have reported total obliteration of malformation with exclusive embolization [45, 46]. Partial obliteration of AVM could be achieved in 54–90% of cases with improvement in clinical condition related to steal syndrome, although risk of bleeding seems to remains unchanged [41]. Patients with high Spetzler and Martin grades (84% >grade 3) are regarded as unsuitable for surgical excision and were considered for embolization in study by Wikholm et al [43].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of AVM in childhood is controversial. Lussenhop and Rosa [41] proposed anatomical grading to compare operative and natural history risk in AVM patients and concluded that in the first 3 decades, risk of surgery is less than the natural course for all patients with grade I and II and for more than half of those in grade III. Surgery is still the treatment of choice in AVM [22, 24, 25, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, occlusion of proximal arterial feeders could prevent entry into the nidus, leaving the nidus unoccluded and active. This often leads to AVM recruitment of deep perforators making surgery ultimately more challenging [35,36]. In 1974, Serbinenko [37] reported on the use of a detachable balloon attached to a flexible flow-directed catheter.…”
Section: Embolization Of Brain Avmsmentioning
confidence: 99%